Caracterização biológica e fisiológica de buva (Conyza bonariensis L.) resistente ao herbicida glyphosate - Kaspary, Tiago Edu (2014)
Conyza bonariensis, popularly known as fleabane, is a major weed of soybean crop in Southern Brazil, due to its evolution as resistant to glyphosate herbicide, high adaptability to production systems and high production of viable seeds. The aim of this work was to investigate the resistance to glyphosate in Conyza bonariensis, from the evaluation of the current level of resistance, alternative herbicides, aspects of growth and development of the resistant biotype when compared to the susceptible to the herbicide, as well as to determine the mechanism of resistance involved. The study was divided in three chapters, with their experiments carried out from May 2012 to July 2013. An experiment of dose-response curve was conducted to determine the level of resistance presented by fleabane. Concurrently, a study evaluated alternative herbicides to glyphosate. During the autumn-winter and spring-summer, there were conducted two experiments of fitness with biotypes susceptible (S) and resistant (R) to glyphosate, where were determined growth variables and yield and quality of seeds. Also, there were developed studies related and not realted to to the target site of the herbicide (EPSPS enzyme), aiming to elucidate the mechanism of glyphosate resistance involved to C. bonariensis specie. The level of resistance observed for fleabane biotype was high, with resistance factor >50. Alternative herbicides to glyphosate were effective in controlling fleabane, proving the non-occurrence of multiple resistance. The R biotype showed higher fitness to the S from variables analyzed, highlighting as superior in the plant height development and dry matter accumulation, besides to conclude the biological cycle in a shorter time than the S biotype. R plants also showed higher quantity and better quality of seeds produced. Thus, the R biotype tends to suppress the S one, even in the absence of the herbicide spray, disseminating the resistance and becaming more difficult the control of fleabane. From the studies related to the mechanism of glyphosate resistance, it is possible to infer the C. bonariensis R biotype shows changes involving EPSPS enzyme, target site of glyphosate, implying in its insensitivity to the herbicide enzyme. Therefore, glyphosate is not anymore a tool in the management of C. bonariensis, being necessary the use of alternative herbicides associated with integrated weed management measures.